A new spectral image assessment based on energy of structural distortion - Cailing Wang; Xuebin Liu; Bingliang Hu (2009 International Conference on Image Analysis and Signal Processing, 2009)
We proposed a new method for assessing spectral image quality. It is based on the energy of structural distortion. We compared it with other assessments which have been used to evaluate spectral image before. Numerical results show that the proposed approach runs well.